Examining the behavioral intention toward using smartphone among the university students in Bangladesh - Ahsan, Syed Mohammad Hasib (IIUC Business Review, 2022)
This study endeavors to explore the factors affecting the behavioral intention toward using smartphone by university students in Bangladesh. In this study, “Technology Acceptance Model” (TAM) and “Theory of reasoned action” (TRA) have been integrated to examine the factors that influence attitude as well as an intention toward using smartphone. Factors used in the basic “Technology Acceptance Model” (TAM) include “Perceived Ease of Use” and “Perceived Usefulness”. “Subjective Norm”, deriving from “Theory of Reasoned Action” (TRA), is integrated with the theoretical framework. In this study, a survey is conducted on 428 students of 10 different universities in Bangladesh. Based on a theoretical framework of the study, a questionnaire is adopted from TAM using a seven point Likert’s scale. Statistical techniques such as multicollinearity test, reliability test, construct and discriminant validity, path analysis, and hypothesis testing are used to analyze the primary data. Findings reveal that “Perceived Ease of Use”, “Perceived Usefulness” along with “Subjective Norm” have significant influence on “Attitude toward using smartphone” that directly impact “Behavioral Intention”. IIUC Business Review, Vol.-11, Issue-1, Dec. 2022, pp. 35-51